Foot self‐care behaviour in type 2 diabetes adults with and without comorbid heart failure - Fekadu Aga; Sandra B. Dunbar; Tedla Kebede; Senbeta Guteta; Melinda Kay Higgins; Rebecca A. Gary (Wiley, 2022)
Abstract Aims To compare the correlates of foot self‐care behaviours among type 2 diabetes mellitus (T2D) adults with and without comorbid heart failure (HF). Design Cross‐sectional, correlational, comparative design. Methods A 210 T2D adults (105 with HF and 105 without HF) participated from August-December 2020. Foot self‐care behaviour was measured using the foot care subscale of the Summary of Diabetes Self‐Care Activities (SDSCA) instrument. A stepwise logistic regression analysis was used to explore variables predicting foot self‐care behaviour. Results The participants' mean age was 58.7 ± 10.9 years. Poor foot self‐care behaviour was reported in T2D adults both with (53.3%) and without (54.3%) HF. Participants with HF‐comorbidity were statistically significantly older and had higher total daily medication intake. Household income and the total number of daily medications statistically significantly predicted foot self‐care behaviour in HF‐comorbid T2D adults. Marital status, social support and body mass index predicted foot self‐care behaviour in the non‐HF group.